QUALIDADE FÍSICA DE UM CAMBISSOLO HÁPLICO ALUMÍNICO SUBMETIDO A DOSES E FORMAS DE APLICAÇÃO DE CALCÁRIO - Santos, José Alfredo Baptista dos (2015)
The objective of this wok was to evaluate the influence of doses and types of application of lime on an Inceptisol Haplustult aluminum cultivated with grains in the city of Irati, Southeast Region of the State of Paraná, Brazil. An experiment was carried out in factorial design 3X4 with 5 replications. The evaluations were performed in a small rural property in the household system, whose main activity is the cultivation of grains, with animal production for beef and milk intended for family consumption.The plots consisted of the types of lime application (surface, plowing+harrowing and chisel plowing+ harrowing), and the sub-plots were the lime doses (0, 10, 15 and 20 Mg ha-1).The evaluations and samplings for physical analyzes were carried out along the cycle of the corn crop (Zea mays) in two years, while collections for chemical evaluations were carried out after the harvest of the corn crop. In both cycles of crops they have been evaluated winter crops dry biomass yields and grain and dry biomass yields for the summer crop. The physical and chemical soil attributes were evaluated in the layers of 0.0-0.10 and 0.10-0.20 m depths. The soil penetration resistance measurements and soil water volumetric content determinations were performed in the field using electronic penetrometer and moisture sensors, respectively. The results for the different doses and types of application of lime were compared by the confidence interval of the averages for the different attributes (P≤0.15). For the chemical attributes they have been observed significant differences regarding the types and doses of application of limestone,while for the physical attributes they were observed significant differences regarding only for the types of application of lime. With reference to the income of crops, in the first cycle they were observed better results in function of doses and types of application of lime. In the second cycle of crops the results of oat biomass exhibited significance in function of doses and forms of application; however, the incomes of biomass and grain maize were severely affected by drought. The largest values of soil resistance to penetration were observed in the incorporation of lime with plowing+harrowing, while the incorporation with chisel plowing+harrowing have been presented lower values of soil bulk density, higher saturation of bases and better income of biomass and grain.